Endoscopic 1½-transseptal approach for pituitary surgery - Cong, Zixiang; Zhu, Junhao; Sun, Huaiyu; Tang, Chao; Yang, Jin; Ma, Chiyuan (Frontiers in Oncology, 2023)
Background: We previously introduced the one-and-a-half (1½) nostril endoscopic transsphenoidal approach (OETA) to reduce the damage to the nasal structures. Here, we reported the modified approach which is called the endoscopic 1½-transseptal approach (EOTA) for pituitary surgery by combining the OETA and the microscopic transseptal approach to simplify intranasal procedures and protect nasal mucosa. In EOTA, we removed the sellar lesions in a corridor that is composed of the right submucosal space and the anterior left ½ nasal cavity. Methods: We reported EOTA with a detailed technical description and preliminary clinical outcomes. A total of 128 patients who underwent EOTA for pituitary surgery from July 2018 to September 2020 were reviewed for evaluation of the safety and efficacy of this approach. Results: EOTA has a high gross total resection (GTR) rate and a 1ow complication rate. GTR was achieved in 106 (82.8%) patients with pituitary lesions, with 81.4% for pituitary adenomas and 93.3% for other non-adenomatous lesions. Post-operative complications included 3 patients (2.3%) with postoperative cerebrospinal fluid leak, 3 patients (2.3%) with diabetes insipidus, 5 patients (3.9%) with anterior pituitary insufficiency and 2 patients (1.6%) with meningitis. In addition, EOTA simplified the intranasal procedures, which led to shortened operation time (67.8 minutes). The results of ASK nasal-12, the Lund-Kennedy score, and the odor identification test showed that patients who underwent EOTA recovered quickly after surgery and the nasal cavity returned to the preoperative condition both apparently and physiologically one month after surgery. Conclusions: EOTA is a sample, safe and effective approach for pituitary lesions, which provides not only a sufficient surgical corridor for 2-surgeon/4- or 3-hands technique but also minimally invasive access to the sellar region.